Treatment of industrial textile wastewater using uf and mf membrane filtration - Chan, See Yi (2023)
Textile industries are one of the greatest wastewater producers as they require a significant amount of water to be used in the dyeing and finishing processes of textile manufacturing. The number of unit operations in the technological process involved in textile industry are the variables that will affect water consumption in the textile industry. As a result, generally, a typical textile plant may consume a volume of water between 100,000 and 300,000 m3 annually. As textiles address a substantial portion of human requirements, it is predicted that by 2050, there will be 160 million metric tonnes, three times as much clothing as there is today. Membrane technology in wastewater treatment is a recent interest arising technique garnering the industrial application's interest, owing to its ease of setup and low energy requirement. Crossflow membrane filtration is commonly used in the industry, attributed to its tangential flow across the membrane mechanism, leading to low fouling. This study investigated the textile wastewater's effluents using crossflow ultrafiltration (UF) and microfiltration (MF) membrane filtration. The effect of the operating parameter in terms of pressure and flow rate of the crossflow system was performed to evaluate its permeate flux performance. The water flux found in UF membrane increase significantly from 156.26 L/m2hr to 591.98 L/m2hr, and the water flux further increases constantly from 4 bar to 10 bar. Additionally, the flowrate positively affects the permeate flux, where the flux was enhanced from 651.01 L/m2hr to 726.08 L/m2hr when the flow rate increase from 2 LPM to 6 LPM. The water flux in MF membrane increases linearly and substantially from 1,046.39 L/m2hr to 4,238.53 L/m2hr with increasing pressure from 2 bar to 10 bar. Conversely, the water flux enhances slightly at the flow rate of 2 LPM to 3 LPM, and further rises sharply from 3 LPM to 5 LPM and lastly, slow down from 5 LPM to 6 LPM. The quality of the permeate after the filtration was adhere to the standard prescribed by the Department of Environmental, Malaysia. The results from this study suggested that crossflow membrane filtration system could be commercially feasible due to its permeate flux performance and superior permeate quality.